The effects of robot's social praise on human responses in 2D game - Fadli, Nursabrina Suraya; Ghazali, Aimi Shazwani; Shamsul Bahrin, Muhammad Ikmal Hakim (Applied Research and Smart Technology (ARSTech), 2022)
Human-Robot Interaction (HRI) is an interaction between humans and robots through verbal and/or non-verbal cues. Studies in the HRI field concern the psychological effect, especially reactance, experienced by humans in decision-making situations with robots. This study applied persuasive attempts to investigate the impact of social praise by a social robot on human psychological reactance in a decision-making situation. The robot socially expressed its recognition (an acknowledgement of the existence) and reassurance (the action of removing someone's doubts) towards humans in a game, namely "Survival in Island". Social praise was expressed verbally in adoring human activities, such as 'Good Job' for following the robot's decision-making suggestions. The study randomly divided the participants into two conditions (social praise: presence vs absence) in a between-subject design study. Besides using questionnaires to measure humans' psychological conditions, the level of stress experienced by humans was also collected using a Galvanic Skin Response (GSR) sensor. The results indicated significant effects of social praise on perceived ease of use toward the robot, perceived intention to use the robot again in the future, perceived belief towards the robot and perceived compliance with the robot's suggestions through MANOVA tests. The study did not find other significant psychological and physiological effects of praise.